Application of Padi Media (Diagram Board) in Improving Learning Motivation and Mathematics Learning Outcomes of Class V Students of Madrasah Ibtidaiyah - Wahdania Rohmatul Laili; Moh Sutomo; Mashudi Mashudi (FKIP - Universitas Riau, 2026)
Mathematics is often perceived as a difficult subject by elementary school students, particularly in understanding abstract concepts such as data processing. Therefore, the use of innovative and engaging learning media is essential to enhance students’ motivation and learning outcomes. This study aimed to examine the effectiveness of PADI (Diagram Board) media in improving learning motivation and mathematics achievement among fifth-grade students at an Islamic Elementary School (Madrasah Ibtidaiyah). The study employed a qualitative case study approach. Data were collected through classroom observations, interviews with teachers and students, and documentation of learning activities. The findings revealed that the implementation of PADI media increased students’ learning motivation, as indicated by higher levels of participation, engagement, enthusiasm, and interaction during classroom activities. The visual and interactive features of the media helped students better understand concepts related to data processing, including bar charts, line graphs, and pie charts. Furthermore, students demonstrated improved comprehension of the learning materials, which contributed to better mathematics learning outcomes. The study concludes that PADI media serves as an effective visual learning tool that promotes active learning, enhances motivation, and supports students’ understanding of mathematical concepts. These findings suggest that PADI media can be considered an innovative instructional resource for improving mathematics learning at the elementary school level.